IMPLEMENTASI K-MEANS, SUFFIX TREE DAN DEWEY DECIMAL CLASSIFICATION UNTUK SHELVING BUKU PERPUSTAKAAN - Syam Gunawan; Aprilio Aprilio; Rhandy Rhandy (Jurnal Algoritma, Logika dan Komputasi, 2019)
STMIK Library Indonesia has a growing number of book collections, and the increasingly diverse types of library collections become very troublesome when it comes to compiling and grouping them with manual methods. But the large collection of books will also make it difficult to manage the location of books in the library so that there are several books that are illegible and not borrowed. Then to solve the problem, a clustering technique will be applied using the K-Means and Suffix Tree methods in the management of books in the library. Clustering technique is a technique of grouping a number of data / objects into clusters (groups) so that in each cluster will contain data as similar as possible Clustering techniques will group book titles according to their categories. Shelving collections or books are activities that organize / put back collections that are finished / read / borrowed on bookshelves that are available based on the prescribed systematic order. The systematic ordering of books generally refers to the classification system used. Usually the classification system is often used by librarians to group collections using Dewey Decimal Classification (DDC).Keywords: Clustering, K-Means, Suffix Tree, Shelving, Dewey Decimal Classification